2012
DOI: 10.1039/c1dt11498k
|View full text |Cite
|
Sign up to set email alerts
|

Lithium complexes supported by tripodal diaminebis(aryloxido) ligands: Synthesis and structure

Abstract: The diaminebis(aryloxido) ligand precursors H(2)L(1) and H(2)L(2) [H(2)L(1) = Me(2)NCH(2)CH(2)N(CH(2)-4-CMe(2)CH(2)CMe(3)-C(6)H(3)OH)(2); H(2)L(2) = Me(2)NCH(2)CH(2)N(CH(2)-4-Me-C(6)H(3)OH)(2)] were synthesized by a straightforward single-step Mannich condensation. Their reactions with 2 molar equivalents of MeLi in thf afforded [Li(4)(μ-L-κ(4)O,N,N,O)(2)(thf)(2)] (1a, L(1); 1b, L(2)) and unexpectedly small amounts (∼9%) of [Li(6)(μ-L-κ(4)O,N,N,O)(2)(μ(3)-Cl)(2)(thf)(4)]·thf (2a·thf; L(1); 2b·thf, L(2)). Stoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…[2][3][4][5][34][35][36] This contrasts with related mono-anionic aminephenolate lithium complexes that still remain relatively unexplored. 6 Furthermore, it has been established that lithium phenolates usually contain square Li 2 39 Following our recently reported work on zinc compounds of piperazinyl aminephenolate ligands, 18 which efficiently initiated the ring-opening polymerization of rac-lactide and ε-caprolactone in a controlled manner, we decided to study the chemistry of related Li complexes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[2][3][4][5][34][35][36] This contrasts with related mono-anionic aminephenolate lithium complexes that still remain relatively unexplored. 6 Furthermore, it has been established that lithium phenolates usually contain square Li 2 39 Following our recently reported work on zinc compounds of piperazinyl aminephenolate ligands, 18 which efficiently initiated the ring-opening polymerization of rac-lactide and ε-caprolactone in a controlled manner, we decided to study the chemistry of related Li complexes.…”
Section: Introductionmentioning
confidence: 97%
“…The phenolate rings are tilted with respect to the plane containing the lithium centres such that they displayed a propeller-like arrangement whose directions are controlled by the coordinated amine of the ligand. The bond lengths Li (1) 34 Crystals of complex 3 were also grown from toluene-hexane at −35°C. The single crystal X-ray analysis shows that 3 crystallizes as a trimetallic species in the triclinic space group P1 and is slightly less symmetric than 1 due to the greater steric demands of L3 compared with L1, and thermal disorder within the tertamyl groups.…”
Section: Synthesis and Solid-state Structuresmentioning
confidence: 99%
“…While, the lithium compounds based on the aryloxido and the mono-amine(aryloxido) ligands are well documented as efficient initiators for the ring-opening polymerization (ROP) of cyclic esters such as lactide and e-lactone [6][7][8], only two diaminebis(aryloxido)-lithium complexes reported by Chen has been proved to show excellent activities toward the ROP of L-lactide in the presence of benzyl alcohol [9]. Additionally, up to date, only few diaminebis(aryloxido)-lithium compounds of general formula [Li 2 (ONNO)] have been fully characterized [9][10][11][12]. Kozak and co-workers showed that isomeric diaminebis(aryloxides), tripodal [Me 2 NCH 2 CH 2 N(CH 2 -2,4-t Bu 2 -C 6 H 2 O) 2 ] 2À and linear (so-called salan) [MeNCH 2 CH 2 NMe (CH 2 -2,4-t Bu 2 -C 6 H 2 O) 2 ] 2À , in the presence of 1,4-dioxane generated lithium complexes that exhibited a 1,4-dioxane bridged dimers arranging in polymeric and dimeric structures in the solid-state, respectively [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the linear diaminebis(aryloxido) ligands by O'Hara reported lithium complexes, tetra-nuclear revealing open ladder-like conformation and dinuclear structure generated by coordinated tmeda molecule [11]. During the course of our investigation into the lithium coordination chemistry involving tripodal diaminebis(aryloxido) ligands [Me 2 NCH 2 CH 2 N(CH 2 -4-R-C 6 H 3 O) 2 ] 2À (R = Me, CMe 2 CH 2 CMe 3 ) which lack substituents in the ortho position, tetranuclear [Li 4 (l-L-j 4 O,N,N,O) 2 (thf) 2 ] compounds with the cubanoid Li 4 O 4 cores were obtained and structurally characterized [12]. Additionally, we have found that addition of LiCl to [Li 4 (l-L-j 4 O,N,N,O) 2 (thf) 2 ] in thf led to the formation of the hexanuclear [Li 6 (l-L-j 4 O,N,N,O) 2 (l 3 -Cl) 2 (thf) 4 ] complexes which adopt the closed ladder-like structure in the solid state and in solution [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation